Alemtuzumab CARE-MS II 5-year follow-up: Efficacy and safety findings. (12th September 2017) - Coles, Alasdair J.; Cohen, Jeffrey A.; Fox, Edward J.; Giovannoni, Gavin; Hartung, Hans-Peter; Havrdova, Eva; Schippling, Sven; Selmaj, Krzysztof W.; Traboulsee, Anthony; Compston, D. Alastair S.; Margolin, David H.; Thangavelu, Karthinathan; et al.
Abstract : Objective: To evaluate 5-year efficacy and safety of alemtuzumab in patients with active relapsing-remitting multiple sclerosis and inadequate response to prior therapy. Methods: In the 2-year Comparison of Alemtuzumab and Rebif Efficacy in Multiple Sclerosis (CARE-MS) II study (NCT00548405), alemtuzumab-treated patients received 2 courses (baseline and 12 months later). Patients could enter an extension (NCT00930553), with as-needed alemtuzumab retreatment for relapse or MRI activity. Annualized relapse rate (ARR), 6-month confirmed disability worsening (CDW; ≥1-point Expanded Disability Status Scale [EDSS] score increase [≥1.5 if baseline EDSS = 0]), 6-month confirmed disability improvement (CDI; ≥1-point EDSS decrease [baseline score ≥2.0]), no evidence of disease activity (NEDA), brain volume loss (BVL), and adverse events (AEs) were assessed. Results: Most alemtuzumab-treated patients (92.9%) who completed CARE-MS II entered the extension; 59.8% received no alemtuzumab retreatment. ARR was low in each extension year (years 3–5: 0.22, 0.23, 0.18). Through 5 years, 75.1% of patients were free of 6-month CDW; 42.9% achieved 6-month CDI. In years 3, 4, and 5, proportions with NEDA were 52.9%, 54.2%, and 58.2%, respectively. Median yearly BVL remained low in the extension (years 1–5: −0.48%, −0.22%, −0.10%, −0.19%, −0.07%). AE exposure-adjusted incidence rates in the extension were lower than in the core study. Thyroid disorders peaked at year 3, declining thereafter. Conclusions: Alemtuzumab provides durable efficacy through 5 years in patients with an inadequate response to prior therapy in the absence of continuous treatment. Classification of evidence: This study provides Class III evidence that alemtuzumab provides efficacy and slowing of brain atrophy through 5 years.